Hunting pressure on cracids (Cracidae: Aves) in forest concessions in Peru - Barrio, Javier (2011)
The impact of timber exploitation on biodiversity is usually increased by hunting in the exploited area. Proper forest management practices on areas under commercial exploitation minimize hunting and damage to the forest. Large species of Cracidae, the most endangered family of birds in the Neotropics, are among the first to be affected in a Neotropical forest damaged by timber-extraction activities, and where at least moderate hunting occurs. Herein an assessment of cracids is carried out in three areas with selective logging in Peru in 2004 and 2005, is used to evaluate hunting pressure. Tree inventory trails were used as transects, and density was calculated using the line transect methodology. Four species of cracids were evaluated, and density was calculated for three of them. The area with lower hunting pressure, Maderyja, showed higher cracid diversity and was the only with the presence of razor-billed curassows (Mitu tuberosum) and blue-throated pining-guans (Pipile cumanensis), two sought-after prey species. Areas where hunting intensity is higher had lower cracid diversity. The density of the M. tuberosum was high in Maderyja: 11.3 ind/km2 (95% CI: 7.4 – 17.3 ind/km2). In contrast, Spix’s guan (Penelope jacquacu) did not show a marked difference among areas, unless compared to heavily hunted sites. The higher diversity of cracids and the density found for razor-billed curassows suggests Maderyja had low hunting pressure in the past and is properly managed towards wildlife. Currently, the Peruvian Amazon is being opened for forestry concessions and hydrocarbons exploitation and proper management towards wildlife is necessary to guarantee the conservation of susceptible taxa such as cracids.